THE SCHOOL AS A TRANSFORMATIVE AGENT IN THE 2030 AGENDA (Editora Impacto Científico, 2025)
This article explores the role of schools as transformative agents in implementing the 2030 Agenda, a global commitment aimed at addressing global challenges through the Sustainable Development Goals (SDGs). The primary objective is to analyze how schools can effectively contribute to achieving these goals by promoting an education that goes beyond knowledge transmission, engaging students and communities in sustainable and conscious practices. The justification for this study lies in the increasing need to integrate the SDGs into education, given that schools play a crucial role in shaping citizens who are prepared to tackle global challenges such as poverty, inequality, and environmental degradation. The role of education is fundamental not only to inform but also to transform attitudes and behaviors, preparing students to become active agents in building a more sustainable and equitable future. The methodology adopted is bibliographic, based on the review and analysis of existing literature on the 2030 Agenda, education for sustainable development (ESD), and the role of schools in social transformation. Academic sources, international organization documents, and relevant publications were selected to provide a comprehensive view of the pedagogical practices and educational policies needed to integrate the SDGs into the school curriculum. The analysis involved identifying key themes, categorizing theoretical and practical approaches, and synthesizing authors' contributions to understanding the role of schools in the 2030 Agenda. The results indicate that, while there is consensus on the importance of schools in implementing the 2030 Agenda, several challenges remain. Integrating the SDGs into the school curriculum requires a systematic and well-planned approach, as well as a review of educational policies to support innovative pedagogical practices. Ongoing teacher training is essential for adopting new approaches and effectively engaging students. Additionally, schools have the capacity to positively influence their communities by adopting sustainable practices and fostering a culture of social and environmental responsibility. In conclusion, for schools to fulfill their role as transformative agents in achieving the 2030 Agenda, a collective effort is needed that includes changes in educational practices, support from educational policies, and active community engagement. Only with an integrated and committed approach will it be possible to transform schools into dynamic centers of social and environmental change.